Susceptibilidad a betalactámicos y caracterización de betalactamasas en cultivos de enterobacteriaceas ambientales del hospital regional de cajamarca, octubre 2009 - junio 2010 - Rivera Jacinto, Marco Antonio (2011)
We performed a descriptive observational study to identify bacteria of the Enterobacteriaceae family that are capable of producing beta-lactamases, contained in nosocomial reservoirs at Hospital Regional de Cajamarca during October 2009 - June 2010. Samples were obtained by swabbing surfaces such as: beds, tables, sinks, faucets and patients’ medical charts of the areas of surgery, pediatrics, medicine, neonatology and intensive care unit (ICU), then were seeded in MacConkey agar and blood agar to isolate and identify Enterobacteriaceae by conventional methods. An antimicrobial susceptibility test was performed for beta-lactamic antibiotics: ampicillin, cephalothin, amoxicillin-clavulanate, cefoxitin, ceftazidime, cefotaxime, ceftriaxone, aztreonam, cefepime, imipenem and meropenem, by screening and confirmation tests was determined the production of classical beta-lactamase (CBL), inducible AmpC (IBL) and extended-spectrum (ESBL); the statistical analysis was performed using SPSS version 17. 125 Enterobacteriaceae clinically relevant were identified, including 31 Enterobacter cloacae, 20 Escherichia coli and 19 Klebsiella pneumoniae, some of them were multidrug resistant. 98 (78.4%) cultures were positive to test for CBL, 29 (23.2%) to IBL and 35 (28%) to ESBL, the number of IBL cultures were significantly higher in surgery and pediatrics, and those with ESBL in neonatology and ICU, the presence of ESBLs cultures on tap-sinks was also significant (p <0.05). Enterobacter sp. was the Enterobacteriaceae with IBL predominant and among the ESBL positive most important were K. pneumoniae, Citrobacter freundii and E. coli. It concludes that many enterobacteria contained in reservoirs inanimate of this hospital have high-level antibiotic resistance, mainly in the areas of neonatology and ICU.